Haemodynamic and End Tidal CO2 Changes State after Inflation and Deflation of Pneumatic Tourniquet on Extremities - Zaman, SM; Islam, MM; Chowdhury, KK; Rickta, D; Ireen, ST; Choudhury, MR; Islam, M (Mymensingh Medical Journal, 2010)
Mymensingh Med J. 2010 Oct;19(4):524-8 The abstract of this article is available on the PubMed website